2006
DOI: 10.1002/chem.200600115
|View full text |Cite
|
Sign up to set email alerts
|

Enantio‐ and Diastereoselective Michael Addition Reactions of Unmodified Aldehydes and Ketones with Nitroolefins Catalyzed by a Pyrrolidine Sulfonamide

Abstract: Chiral (S)-pyrrolidine trifluoromethanesulfonamide has been shown to serve as an effective catalyst for direct Michael addition reactions of aldehydes and ketones with nitroolefins. A wide range of aldehydes and ketones as Michael donors and nitroolefins as acceptors participate in the process, which proceeds with high levels of enantioselectivity (up to 99 % ee) and diastereoselectivity (up to 50:1 d.r.). The methodology has been employed successfully in an efficient synthesis of the potent H(3) agonist Sch 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
58
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(65 citation statements)
references
References 87 publications
7
58
0
Order By: Relevance
“…A related study by Enders showed a strong solvent effect in the reaction since in MeOH the enantioselectivity could be increased to 76% for the major syn diastereomer in the reaction between 3-pentanone and trans-β-nitrostyrene employing a 20 mol% of Lproline as catalyst. [7] Since these preliminary studies, very effective catalytic systems (2-20) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have been developed for the asymmetric Michael reaction of ketones with nitroalkenes being the process generally syn-selective (Scheme 1). Best improvements to this reaction have been mostly achieved using pyrrolidine-based catalytic derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related study by Enders showed a strong solvent effect in the reaction since in MeOH the enantioselectivity could be increased to 76% for the major syn diastereomer in the reaction between 3-pentanone and trans-β-nitrostyrene employing a 20 mol% of Lproline as catalyst. [7] Since these preliminary studies, very effective catalytic systems (2-20) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have been developed for the asymmetric Michael reaction of ketones with nitroalkenes being the process generally syn-selective (Scheme 1). Best improvements to this reaction have been mostly achieved using pyrrolidine-based catalytic derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, catalyst 15 and the fluorous sulfonamide 19 can be easily recycled by precipitation and fluorous solid-phase extraction, respectively, and reused without significant loss of activity and stereoselectivity. [7] up to 76% ee 2 [8] up to 81% ee 3 [9] up to 99% ee [18] up to 86% ee 13 [19] up to 91% ee up to 91% ee 5 [11] up to 68% ee 6 [12] up to 92% ee 7 [13] up to 94% ee 8 [14] up to 87% ee 9 [15] up to 98% ee 10 [16] up to 98% ee 11 [17] up to 91% ee 14 [20] up to 98% ee 15 [21] up to 99% ee 16 [22] up to 90% ee 17 [23] up to 99% ee 18 [24] up to 99% ee 20 [26] up to 97% ee 19 [25] up to 95% ee …”
Section: Introductionmentioning
confidence: 99%
“…The absolute stereoconfiguration of the product 3a was determiend based on the comparision of the optical rotation of its known counterpart. [11] [a] Isolated yield. [b] Determined by chiral HPLC analysis (Chiralpak AS-H).…”
mentioning
confidence: 99%
“…[2][3][4][5] In particular, O-TMS-protected diphenylprolinol (1; TMS= trimethylsilyl), [6] pyrrolidinesulA C H T U N G T R E N N U N G fon-A C H T U N G T R E N N U N G amide 2 (Tf = trifluoromethanesulfonyl) [7] and trans-4-hydroxyprolylamide 3 [8] ( Figure 1) act as effective organocatalysts for this class of reactions, affording almost complete enantioselectivities.…”
mentioning
confidence: 99%